2013
DOI: 10.1016/j.febslet.2013.03.030
|View full text |Cite|
|
Sign up to set email alerts
|

Vangl2, the planner cell polarity protein, is complexed with postsynaptic density protein PSD‐95

Abstract: Edited by Maurice Montal Keywords:Dendritic spine PCP protein PDZ-binding motif Prickle2 Synapse Van Gogh-like protein a b s t r a c tVangl is a component of the non-canonical Wnt/planar cell polarity pathway, which is implicated in various cell polarity functions. However, little is known about its synaptic localization in neurons. Here, we show that Vangl1 and Vangl2 are expressed in adult rat neurons, where they are tightly associated with the postsynaptic density (PSD) fraction. Vangl2 forms a complex with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…As dendritic spines are the specific subcellular site of glutamatergic synapses in pyramidal neurons, these data are consistent with previous findings that Vangl2 localizes to the postsynaptic compartment of glutamatergic synapses, where it interacts with PSD95, transsynaptic adhesion molecules and the PCP pathway protein Prickle2 [14,15,16]. Our genetic data corroborate previous reports of similar phenotypes following shRNA-mediated knockdown of Vangl2 in cultured neurons [15,33] and have allowed us to compare and contrast neurodevelopmental phenotypes induced by two molecularly distinct (engineered null vs. spontaneous missense) alleles at this locus.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As dendritic spines are the specific subcellular site of glutamatergic synapses in pyramidal neurons, these data are consistent with previous findings that Vangl2 localizes to the postsynaptic compartment of glutamatergic synapses, where it interacts with PSD95, transsynaptic adhesion molecules and the PCP pathway protein Prickle2 [14,15,16]. Our genetic data corroborate previous reports of similar phenotypes following shRNA-mediated knockdown of Vangl2 in cultured neurons [15,33] and have allowed us to compare and contrast neurodevelopmental phenotypes induced by two molecularly distinct (engineered null vs. spontaneous missense) alleles at this locus.…”
Section: Discussionsupporting
confidence: 92%
“…The four-pass transmembrane protein Van Gogh-like 2 (Vangl2) is a key player in the PCP pathway and interacts with several proteins that influence synapse formation, including other PCP proteins such as Dishevelled (Dvl) [12] and Dapper-antagonist of catenin-1 (Dact1) [13] as well as the postsynaptic protein PSD95 [14,15,16]. Vangl2 also participates in signaling upstream of small GTPases [17,18] regulating cytoskeletal dynamics crucial to dendrite and dendritic spine formation and plasticity [19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Van Gogh and Fz affect neurite growth independently in Drosophila (54), and Van Gogh, Prickle, and Dishevelled mutant neurons in Caenorhabditis elegans display supernumerary neurites (62). An additional role of Vangl2 in synapse formation was recently demonstrated (63,64). These observations suggest that Vangl1,2 are likely to affect brain development by acting in different pathways, in addition to epithelial PCP.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical and molecular analyses revealed that Vangl2 binds directly to N-cadherin [198,199], the transmembrane protein that facilitates the initial critical adhesive event between presynaptic and postsynaptic elements, to mediate its endocytic removal from the membrane [199]. Vangl2 and Prickle2 also bind and promote postsynaptic clustering of PSD95, critical for maintenance of synaptic integrity [199,227,228]. Prickle1 was found to regulate synaptogenesis and synaptic vesicle trafficking through a direct interaction with synapsin1 (Syn1) [229]; the synapsin protein family have important roles in synapse formation and neurotransmitter release and have previously been implicated in the pathogenesis of psychiatric disorders [230,231,232,233,234,235,236].…”
Section: Synapse Formation and Functionmentioning
confidence: 99%